Introductory microbiology lab skills and techniques in food science - Shen, Cangliang; Zhang, Yifan (London Academic Press, an imprint of Elsevier, 2022)
"Introductory Microbiology Lab Skills and Techniques in Food Science covers topics on isolation, identification, numeration and observation of microorganisms, biochemistry tests, case studies, clinical lab tasks, and basic applied microbiology. The book is written technically with figures and photos showing details of every lab procedure. This is a resource that is skills-based focusing on lab technique training. It is introductory in nature, but encourages critical thinking based on real case studies of what happens in labs every day and includes self-evaluation learning questions after each lab section. This is an excellent guide for anyone who needs to understand how to apply microbiology to the lab in a practical setting"--
1. Introduction of microbial and chemical safety and lab notebook record -- 2. Practice of bright-field microscope -- Preparation of smears and simple stain practice -- Gram-stain practice -- 5. Acid-fast practice -- 6. Endospore stain practice -- 7. Aseptic technique-bacteria transfer and streak plating -- 8. Lab practice test 1- identify unknown bacteria using gram-stain -- 9. Introduction of bacteria medium, nutritional requirements (synthetic and complex media), selective & differential media (MacConkey, mannitol salt, blood agar) -- 10. Lab practice test 2 - dilution technology and quiz -- 11. Numeration bacteria population by pour plating -- 12. Numeration bacteria population by spread plating -- 13. External conditions for bacteria growth (temperature, pH, oxygen, osmotic) 14. Cultivation of anaerobic bacteria 15. Biochemistry test of bacteria-1 (urease test, carbohydrate fermentation, catalase test, oxidase test) -- 16. Biochemistry test of bacteria-2 (nitrate reduction, decarboxylation, & deamination of amino acids, IMViC test, hydrogen sulfide, motility, and indole test) -- 17. Biochemistry test of bacteria-3 (API20e and Enterotube II) -- 18. Extracellular enzymatic activities of microorganisms -- 19. Case study 1 (bacteria cause upper respiratory tract diseases) -- 20. Clinical lab practice-urine sample bacteria isolation -- 21. Case study 2. (bacteria cause intestinal tract diseases) -- 22. Isolation of phage and plaque forming units determination -- 23. Antibiotic susceptibility testing and evaluation of antiseptic/disinfectants -- 24. Microbial counts of food product -- 25. Total plate counts & coliform counts of pond water.
Includes index.
Keywords: Food -- Microbiology -- Laboratory manuals; Food -- Microbiology -- Technique